Evaluating learning centered school leadership - Marcos Sarasola Bonetti; Carolina da Costa (Pontificia Universidad Católica del Perú, 2016)
The research shows that school leadership influences school management results in general, and it particularly impacts student learning. This article presents and analyzes the VAL-ED (Vanderbilt Assessment of Leadership in Education) as a school leadership assessment tool that is based on the research on learning centered leadership.